2017
DOI: 10.1590/0001-3765201720160298
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds from Mexican Medicinal Plants as Potential Drug Leads for Anti-Tuberculosis Drugs

Abstract: In Mexican Traditional Medicine 187 plant species are used in the treatment of respiratory conditions that may be associated with tuberculosis. In this contribution, we review the ethnobotany, chemistry and pharmacology of 63 species whose extracts have been assayed for antimycobacterial activity in vitro. Among these, the most potent is Aristolochia brevipes (MIC= 12.5 µg/mL), followed by Aristolochia taliscana, Citrus sinensis, Chrysactinia mexicana, Persea americana, and Olea europaea (MIC<64 µg/ mL). Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Mexicoʼs outstanding biodiversity and well-conserved knowledge of traditional medicine makes the country a good starting point for such an endeavor. At least 187 species are ethnobotanically used to treat TB-related symptoms, but only onethird of these plants have been experimentally tested against Mycobacterium tuberculosis [5]. The Los Tuxtlas Biosphere Reserve in the state of Veracruz harbors the most important remains of the tropical rainforest that once covered a great part of the Gulf Coast of Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…Mexicoʼs outstanding biodiversity and well-conserved knowledge of traditional medicine makes the country a good starting point for such an endeavor. At least 187 species are ethnobotanically used to treat TB-related symptoms, but only onethird of these plants have been experimentally tested against Mycobacterium tuberculosis [5]. The Los Tuxtlas Biosphere Reserve in the state of Veracruz harbors the most important remains of the tropical rainforest that once covered a great part of the Gulf Coast of Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…These natural compounds (secondary metabolites) have been utilized and chemically modifi ed by humans since ancient times to treat and cure their diseases [21]. A quick search of the literature (the main stream natural products journals and PhD theses from university libraries) could give an estimate of >10000 unique compounds which have been previously isolated from natural products (fl ora, algae and fauna).…”
Section: Socio-economic Need Of Anti-tb Natural Productsmentioning
confidence: 99%
“…3-α-tigloyl-melianol has no toxicity on Vero cells which is very important for further research [16]. [5][6][7][8] South America is another huge area where folk medicine is the main treatment. Allophylus edulis is an endemic plant of the region which is commonly known as a good anti-inflammatory remedy.…”
Section: Extracts and Natural Substances Isolated From Plantsmentioning
confidence: 99%
“…Researchers isolated pure compounds and found that the most active of them was 1'-acetoxychavicol acetate, isolated from Alpina galangal with an MIC value of 0.024 µg/ml [7]. In Mexico, healers use 187 plants to treat respiratory diseases that may be associated with tuberculosis, 63 of which have been assayed for anti-mycobacterial activity [8]. Traditional medicine is simply one approach to treatment and seems to be ineffective, in fact, people from undeveloped areas, without access to medicines and physicians, have to rely on traditional medicinal practitioners.…”
Section: Introductionmentioning
confidence: 99%